Isolation and Bioactivities of Main Functional Components in Tea: A Review - Sun, T.; Pan, B.L.; Huo, Y.; Guan, S.M.; He, Y. (Asian Journal of Chemistry, 2014)
The main functional components of tea consist of theanine, g-amino butyric acid, tea polysaccharides, tea polyphenols and caffeine. These functional components contribute to the health benefits for humans mainly through drinking tea, which include anti-oxidation, anti-virus, cancer prevention, blood pressure and blood fat adjustment, learning and memorizing capacities improvement, immunity enhancement, etc., along with the unique and pleasant aroma and flavor, which make tea the most popular beverage around the world. This paper presents a review on the isolation and bioactivities of these functional components naturally existing in tea.